The Effect of Promotion, Service Quality, and Price Perception on Gojek Customer Satisfaction - Jureid Jureid; Rizka Ar Rahmah; Erni Yusnita Siregar (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study explores how service quality, promotion, and price perception impact customer satisfaction with Go-Jek in Medan, using a quantitative approach with data gathered from questionnaires and interviews among 40 users who had used the Go-Jek app more than five times. The findings indicate that service quality does not significantly affect customer satisfaction, with a t-value of 2.437 exceeding the critical value of 1.688 and a significance level of 0.020. Conversely, promotions negatively influence customer satisfaction, evidenced by a count value of -0.639 compared to the critical value of 1.688 and a significance level of 0.527. Price perception, however, positively correlates with customer satisfaction, as shown by a count value of 5.942 surpassing the critical threshold of 1.688 and a significance of 0.000. Collectively, these factors significantly affect customer satisfaction, with an F-count of 82.143 against an F-table value of 2.87 and a significance of 0.000. The adjusted R-squared value of 0.862 (86.2%) indicates that these variables explain a majority of the variance in customer satisfaction, with the remaining 13.8% attributed to other unexamined factors.